2017
DOI: 10.3140/bull.geosci.1648
|View full text |Cite
|
Sign up to set email alerts
|

Palaeozoic evolution of animal mouthparts

Abstract: During the Palaeozoic, a diversification in modes of life occurred that included a wide range of predators. Major macroecological events include the Cambrian Explosion (including the Agronomic Substrate Revolution and the here introduced 'Ediacaran-Cambrian Mouthpart Armament'), the Great Ordovician Biodiversification Event, the Palaeozoic Plankton Revolution, the Siluro-Devonian Jaw Armament (newly introduced herein) and the Devonian Nekton Revolution. Here, we discuss the evolutionary advancement in oral equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
(52 reference statements)
1
31
0
Order By: Relevance
“…The late Palaeozoic saw turnover in a number of vertebrate clades, which resulted in an abundance and diversity of durophagous predators (Sallan & Coates ; Klug et al . ). This enhanced predation from durophagous predators has been tied to the evolution of anti‐predatory strategies in crinoids (Sallan et al .…”
Section: Discussionmentioning
confidence: 97%
“…The late Palaeozoic saw turnover in a number of vertebrate clades, which resulted in an abundance and diversity of durophagous predators (Sallan & Coates ; Klug et al . ). This enhanced predation from durophagous predators has been tied to the evolution of anti‐predatory strategies in crinoids (Sallan et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has been indicated that mouth size is also important in increasing sediment reworking because small mouths tend to be associated to selective ingestion of small volumes or organic-rich detritus 29 . Although any discussion of mouth size of the producer of Parapsammichnites would be completely speculative, we note that the Ediacaran–Cambrian transition has been regarded as a time of significant evolution in metazoan mouthparts, albeit in connection with predation rather than deposit feeding 67 .…”
Section: Discussionmentioning
confidence: 93%
“…The works comprising this volume include, on one hand, those contributions of Colmenar et al (2017) and Pereira et al (2017) focused on the study of the Ordovician faunas (mainly brachiopods and trilobites) from Portugal, Spain, Czech Republic and Morroco; and secondly the contributions of Lu et al (2017), Chevrinais et al (2017) and Klug et al (2017), all of them focused on the Devonian Period including two main approaches, conodont biostratigraphy (Lu et al 2017), and palaeoecology (Chevrinais et al 2017, Klug et al 2017.…”
Section: Special Issue Contributionsmentioning
confidence: 99%
“…The most interesting conclusion of this work is that the Devonian vertebrate communities were organized in multiple trophic levels, comparable to those of recent aquatic ecosystems, showing a consistency of aquatic food web structure across geological time, and indicating that size-based feeding interactions were established early in vertebrate history. This interesting palaeoecological paper, is completed by the study of Klug et al (2017) describing a new major macroecological event during the Silurian-Devonian times, the so-called Siluro-Devonian Jaw Armament in relationship with the Palaeozoic Plankton Revolution and the Devonian Nekton Revolution. Klug et al (2017) discuss the evolutionary advancement in oral equipment, i.e.…”
Section: Special Issue Contributionsmentioning
confidence: 99%
See 1 more Smart Citation